Diseño de adaptaciones curriculares en la educación superior para estudiantes con discapacidad psicosocial de la Universidad Nacional de Loja, periodo 2024. - Bermeo Guaya, Katy Yadira (2024)
This research paper was aimed at characterising the design of curricular adaptations made by teachers for students with psychosocial disabilities at the Universidad Nacional de Loja, as well as to identify the challenges and barriers that hinder the design of such curricular adaptations and to propose a curricular adaptations design for this group of students. A mixed-method approach was employed, along with a non-experimental descriptive design and a cross- sectional cut, using a non-probabilistic sample. Surveys and semi-structured interviews were used to collect data from teachers and personnel from the University Welfare department. The results showed that teachers use various strategies in the design of curricular adaptations, but their quality and effectiveness vary due to a lack of specific training and adapted resources. Additionally, barriers and challenges were identified, such as limited understanding of students' needs, lack of specialized training, and the absence of manuals, guides, or protocols to guide the development of curricular adaptations. Therefore, it was recommended to implement ongoing training events for teachers, as well as the creation of a manual for designing curricular adaptations to ensure sustainability and long-term effectiveness.